SHP2 Inhibitors Show Anti-Myeloma Activity and Synergize With Bortezomib in the Treatment of Multiple Myeloma - Zhou, Pan; Xiao, Mengyu; Li, Weiya; Sun, Xiaobai; Bai, Yanliang; Meng, Feiying; Zhu, Zunmin; Yuan, Weiping; Sun, Kai (Frontiers in Pharmacology, 2022)
Multiple myeloma (MM) is a plasma cell malignancy that remains incurable. The protein-tyrosine phosphatase SHP2 is a central node regulating RAS/mitogen activated protein kinase (MAPK)/extracellular signal regulated kinase (ERK) signaling pathway, which plays a crucial role in the pathogenesis and proteasome inhibitor (PI) resistance of MM. Several pre-clinical studies have demonstrated that SHP2 inhibitors exerted anti-tumor activity in cancer harboring diverse mutations in RAS pathway, offering the potential for targeting myeloma. In this study, we showed that pharmacological inhibition of SHP2 activity using SHP099 and RMC-4550 efficiently inhibited the proliferation of MM cells by inducing apoptosis and cell cycle arrest. Mechanismly, SHP2 inhibitors activated the level of cleaved caspase3, BAK and P21 as well as downregulated ERK phosphorylation in MM cells. Moreover, blockade of SHP2 exhibited anti-myeloma effect in vivo in a mouse xenograft model. Additionally, SHP2 inhibitors synergized the antineoplastic effect of bortezomib in bortezomib sensitive MM cells and showed identical efficacy in targeting bortezomib resistant MM cells. Overall, our findings suggest that SHP2-specific inhibitors trigger anti-myeloma activity in vitro and in vivo through regulating ERK pathway, as well as enhances cytotoxicity of bortezomib, providing therapeutically benefit for both bortezomib naïve and resistant MM.